What is the level of nutrition literacy of Saudi adolescents? A national wide exploratory cross-sectional study - Bookari, Khlood (Frontiers in Nutrition, 2023)
Background Despite being a prolific research topic, studies evaluating nutrition literacy in the Arab world are scant and still nonexistent in the Kingdom of Saudi Arabia. Therefore, a national study was launched with the aim to (1) assess nutrition literacy among Saudi adolescents aged 10–19 years old and (2) determine its correlates. Methods A cross-sectional study was launched across all Saudi provinces between 29 April and 6 June 2022, enrolling a convenience sample of 2,115 adolescents (mean age = 16.8 ± 2.5; girls: 48.7%). An online self-administered questionnaire was disseminated to eligible participants to collect relevant data. Results Study findings showed that nearly half of the adolescents (44.6%) had poor nutrition literacy. The male gender doubled the risk of adolescents having poor nutrition literacy (OR = 2.0, CI = 1.5-2.5, p < 0.001). Northern border residents were 14 times more likely to be nutritionally illiterate, in contrast to adolescents residing in Riyadh (OR = 14.0, CI = 7.3–28.0, p < 0.001). Adolescents were more likely to be nutritionally illiterate if they were underweight or overweight (OR = 2.7, CI = 1.6–4.7, p < 0.001; OR = 2.2, CI = 1.7–2.9, p < 0.001). School students had 2 times more risk of having poor nutrition literacy, in contrast to those who were enrolled in universities (OR = 1.8, CI = 1.4–2.4, p < 0.001). Nutrition illiteracy was 4 times higher among adolescents having caregivers else than their parents (OR = 3.9, CI = 2.2–6.9, p < 0.001). Parental education level also contributed to determining adolescents' nutrition literacy status. Conclusions It has become essential to courage the development of supportive school environments in Saudi Arabia to promote nutrition education and improve adolescents' nutrition literacy. Without a doubt, this calls for taking a holistic approach on the part of education and health ministries, nutrition professionals, educators, parents, and, most importantly, the teenagers themselves, who must have the desire and motivation to learn.